Marketing strategy - Fifield, Paul (Oxford: Butterworth-Heinemann, 1998)
Marketing Strategy strips away the confusion & jargon that surround what ought to be one of the most straightforward areas of modern business. Marketing & strategy are about relationships between people & this is brought into focus in the text